REKAYASA TEKNOLOGI PENGOLAHAN IKAN TEMBANG (Sardinella Sp) MENJADI BEBERAPA PRODUK KOMERSIL DALAM RANGKA MENINGKATKAN NILAI JUAL PRODUK PERIKANAN - Amrah Husna; Muhammad Khidri Alwi; Winarno Arifin (Fakultas Perikanan dan Ilmu Kelautan Universitas Muslim Indonesia Makassar, Sulawesi Selatan, 2019)
The optimum effort effort in fishing activities and the actual level of utilization of tembang fish resources in the Makassar Strait waters are increasing every day.Based on the reality conditions above, in order to increase the selling value of tembang fish to further increase the income of fishermen, engineering research on tembang fish processing technology is needed into several commercial products with more modern processing methods and can be stored in a relatively long time and sell well on standard markets. national and international.The purpose of this study was to find out how the practical method of processing tembang fish into canned fish, fish sauce and fish silage, is a standard home industry that has high economic value and relatively long lasting power. The urgency of this study is expected to be a basic knowledge of the community in order to increase the selling value of tembang fish as a fishery product with high economic value that can improve the standard of living of the community.The processing method carried out is a combination of traditional methods and modern methods, including methods of cooking, fermentation, salting, enzyme use, sterilization, and packaging systems to produce processed products that are of high quality and have high selling value. Data analysis to be carried out for quantitative data is analysis of variance (complete randomized design) and for qualitative data observed by organoleptic test and processed by descriptive method. Processed products produced in this study are fish sauce, canned fish and fish silage.